Análise da microestrutura, parâmetros térmicos e de propriedades mecânicas na solidificação direcional de ligas Al-Mg-Fe - Gomes, Leonardo Fernandes (2017)
Al-Mg-Fe alloys are appointed as favorable ones in respect of the costs involved and all the required properties for successful vessel service. However, experimental inter-relations of solidification thermal parameters, microstructure and mechanical resistance are still undetermined. In the present research work, the dependences of tensile properties on the length scale of the dendritic morphology of ternary Al-1.2wt.%Mg-1.5wt.%Fe and Al-7.0wt.%Mg-1.5wt.%Fe alloys are examined. Transient heat flow conditions during solidification have been achieved by the use of a directional solidification system, thus permitting a comprehensive characterization of the dendritic microstructures to be performed. Thermo-Calc computations, X-ray diffraction (XRD) and scanning electron microscopy (SEM) analyses were carried out to give support to the extensive microstructural evaluation performed with both ternary Al-Mg-Fe alloys. Experimental growth relations of primary, λ1 and secondary, λ2 dendrite arm spacings with cooling rate (ṪL) and of tensile properties with λ2 are proposed. For both alloys examined, Hall-Petch type formulae show that the tensile strength increase with the decrease in λ2. The soundest strength-ductility balance is exhibited by the Al-7.0wt%Mg-1.5wt%Fe alloy specimen with very refined microstructure. This is shown to be due to a more homogeneous distribution of intermetallic particles in connection with solid solution strengthening propitiated by Mg. Functional experimental inter-relations of tensile properties with growth (VL) and cooling rates (ṪL) for both ternary Al-Mg-Fe alloys have also been derived.